Improved Synthesis of No-Carrier-Added [*I]MIBG and Its Precursor - Hammerschmidt, Friedrich; Kvaternik, Herbert; Schweifer, Anna; Mereiter, Kurt; Aigner, Reingard M. (Synthesis, 2012)
3-(Trimethylstannyl)benzyl alcohol was coupled in a Mitsunobu reaction with bis(Boc)-guanidine to give bis(Boc)-protected 3-(trimethylstannyl)benzylguanidine used as precursor for [*I]MIBG. Radioiodination with [131I]iodine generated from [131I]NaI and chloramine-T, removal of Boc groups, and purification by HPLC gave no-carrier-added tracer [*I]MIBG (81% radiochemical yield, 99% chemical purity) used for imaging tumors of neuroendocrine origin. The structures of bis(Boc)-guanidine and bis(Boc)-protected 3-(trimethylstannyl)benzylguanidine were secured by single crystal X-ray structure analyses.
Keywords: Mitsunobu reaction; electrophilic aromatic substitution; medicinal chemistry; [131I]iodine; halogenation